1998
DOI: 10.1046/j.1365-2958.1998.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ptsG, the gene for the major glucose PTS transporter in Escherichia coli, is repressed by Mlc and induced by growth on glucose

Abstract: SummaryThe gene for the glucose-specific transporter of the phosphotransferase system, ptsG, is expressed from two promoters separated by 141 bp. The expression of the major, shorter transcript is very strongly dependent upon cAMP/CAP. However, unlike other CAPactivated genes, the expression of ptsG is higher in glucose media than in glycerol, implying that ptsG is controlled by a glucose-inducible regulator. A mutation in the mlc gene greatly enhances ptsG expression in a glycerol-grown culture but has no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
146
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(149 citation statements)
references
References 44 publications
3
146
0
Order By: Relevance
“…The ArcA-Pbinding site I, which centered at ϩ1.5, overlapped the P1 promoter. It has been well known that the cAMP⅐CRP complex binds to the ptsG promoter centered at Ϫ40.5 and Ϫ95, respectively (15). The binding sites II (centered at Ϫ51.5) and III (centered at Ϫ97.5) of ArcA-P overlapped these two CRP-binding sites, respectively (Fig.…”
Section: Ligand Fishing Experiments Shows That Arca Specifically Bindsmentioning
confidence: 87%
See 2 more Smart Citations
“…The ArcA-Pbinding site I, which centered at ϩ1.5, overlapped the P1 promoter. It has been well known that the cAMP⅐CRP complex binds to the ptsG promoter centered at Ϫ40.5 and Ϫ95, respectively (15). The binding sites II (centered at Ϫ51.5) and III (centered at Ϫ97.5) of ArcA-P overlapped these two CRP-binding sites, respectively (Fig.…”
Section: Ligand Fishing Experiments Shows That Arca Specifically Bindsmentioning
confidence: 87%
“…1, we found that ArcA as well as CRP bound to the two promoter regions, but not to the ORF of ptsG, to a significant level, implying specific binding of these two proteins to the promoter regions. Although it is not surprising that CRP shows specific binding to the two promoters, since its binding sites to the promoters are well characterized (15,18), it is intriguing that ArcA binds specifically to the two promoters.…”
Section: Ligand Fishing Experiments Shows That Arca Specifically Bindsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose, a representative PTS sugar, mediates transcriptional activation of several genes for PTS-related sugar transporters and some enzymes involved in glycolysis (1, 6). Mlc, a tetrameric protein (7), is a signaling mediator for glucose induction of several PTS operons and related genes (8)(9)(10)(11)(12)(13)(14).A unique feature of induction of the Mlc regulon by glucose is that the effector molecule modulating Mlc activity is a membranebound protein, EIICB Glc (7,15,16), in which cytosolic EIIB protein is attached to membrane-embedded EIIC protein through a linker of Ͼ20 aa. In the absence of glucose, EIICB Glc mainly exists in the phosphorylated form (pEIICB Glc ).…”
mentioning
confidence: 99%
“…Glucose, a representative PTS sugar, mediates transcriptional activation of several genes for PTS-related sugar transporters and some enzymes involved in glycolysis (1, 6). Mlc, a tetrameric protein (7), is a signaling mediator for glucose induction of several PTS operons and related genes (8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%